MiRNA-142-3P and FUS can be Sponged by Long Noncoding RNA DUBR to Promote Cell Proliferation in Acute Myeloid Leukemia - Yin, Zhao; Shen, HuiJuan; Gu, Chun ming; Zhang, Ming qi; Liu, Zhi; Huang, Jing; Zhu, Yangmin; Zhong, Qi; Huang, Yizhen; Wu, Feima; Ou, Ruiming; Zhang, Qing; et al. (Frontiers in Molecular Biosciences, 2021)
Acute myeloid leukemia (AML) is the most common type of acute leukemia in adults. Despite the significant progress being made in this field, the pathogenesis of AML is still not fully understood. Herein, we report the biological role of the miRNA-142-3P and lncRNA DUBR in the pathogenesis of AML and the underlying mechanism. The results showed that lncRNA DUBR was highly expressed in AML, resulting in poor prognosis, especially in M4 AML. In vitro studies elucidated that knockdown of DUBR with small interfering RNA resulted in the suppression of survival and colony formation ability, as well as induction of apoptosis, in AML cells. The DUBR target proteins and microRNAs (miRNAs) were identified using a combination of computational prediction and RNA pull-down, The results revealed that DUBR sponge with miRNA-142-3P and interact with FUS protein. MiRNA-142-3P have a negative correlation with DUBR and overexpression of miRNA-142-3P inhibited cell growth in AML. Meanwhile, DUBR promoted the expression of FUS protein, targeting FUS significantly inhibits the cell growth and promoted cell apoptosis in AML cell lines. Collectively, lncRNA DUBR sponge miRNA-142-3P and bind FUS to regulate angiogenesis of AML. Our work provides new insights into the molecular mechanisms of AML.